Overview of Organizational Factors on Cadre Performance in the Implementation of Posyandu Toddler - Ramadhan, Zulfa Nur Alifa; Herawati, Yennike Tri (Adi Husada Nursing Journal, 2024)
Cadres at Sucopangepok village play a crucial role in reducing stunting by educating about essential practices for toddlers, such as exclusive breastfeeding, proper complementary feeding, and maintaining hygiene to ensure adequate nutrition and prevent infections. The cadres offer health nutrition education to pregnant women and parents of toddlers by monitoring their growth at the posyandu, helping to detect stunting early. They serve as the primary line of defense in improving public health, as they understand their community's characteristics. This study aimed to describe organizational factors on performance in implementing posyandu for toddlers. This study used descriptive research to describe organizational factors including infrastructure, rewards, job design, and leadership on cadre performance. Involved 45 cadres as respondents taken by total sampling. Data was collected using interviews questionnaires, observation, and documentation, then the data was analyzed using descriptive data analysis which will describe the characteristics of each. Facilities infrastructure and work design have good results even though in the facilities and infrastructure, there are facilities that need to be replaced and repaired. The rewards in the category are inappropriate. Leadership is in the adequate category due to the lack of closeness between the leader and the cadres. Cadre's performance during toddler posyandu activities showed promising results. The description of organizational factors in facilities and infrastructure and job design is good, rewards in the category are inappropriate, and leadership is in the adequate category with good cadre performance.